Rhododendrons in Uttarakhand: Diversity and Conservation - Iqbal, Kaiser; Negi, A. K. (International Journal of Environment, 2017)
Rhododendron is a very widely distributed genus, occurring throughout most of the Northern Hemisphere except for dry areas, and extending into the Southern Hemisphere in southeastern Asia and northern Asia with 1200 species. In India, Rhododendrons are represented by 80 species with 10 subspecies and 14 varieties most of which are widely distributed in the Himalayas at an altitude ranging from 1500 – 5500 m. During the course of a revisionary study of Rhododendrons in Uttarakhand, an attempt has been made to collect information on the uses of different species from the field through personal communications with the inhabitants of the remote villages and through repeated inquiries from local folk. Besides of its immense horticultural importance, about 6 species have been recorded here which are used by the local people in different ways. Some species are also found poisonous. The paper deals with the enumeration of these species, their vernacular names, distribution and abundance, uses and methods of utilization. Natural calamities anthropogenic activities such as deforestation, unsustainable extraction for firewood pose a serious threat to Rhododendrons. INTERNATIONAL JOURNAL OF ENVIRONMENT Volume-6, Issue-1, Dec-Feb 2016/17, page: 31-45